Identification of an OprD and blaIMP Gene-mediated Carbapenem Resistance in Acinetobacter baumannii and Pseudomonas aeruginosa among Patients with Wound Infections in Iraq - Al-Ouqaili, Mushtak T. S. (Asian Journal of Pharmaceutics (AJP), 2018)
Objectives and Background: The presence of Acinetobacter baumannii and Pseudomonas aeruginosa as nosocomial pathogens in, especially, debilitated patients inside intensive care units creates the risk of multidrug-resistant infections. The study aimed for the molecular analysis for non-enzymatic mechanisms of antibiotic resistance â€œouter membrane protein (OMP) (OprD Gene)â€ and the blaIMP gene encoding for metallo-beta-lactamase (MBL) with specific primers by polymerase chain reaction, among study isolates of A. baumannii and P. aeruginosa isolates. Patients and Methods: A total of 213 patients were studied during the period from April 2011 to June 2012. 182 of 213 patients were culture positive (88.26%). 44 A. baumannii were presumptive MBL producer isolates. Nine Pseudomonas ssp. isolates were chosen for this study. Results: All isolates (100%) of Acinetobacter baumannii of 44 presumptive MBL producer isolates were positive for the OprD gene. Four (44.44%) Pseudomonas spp. of 9 presumptive MBL producer isolates were positive for OprD gene using CR. 12 (27.3%) A. baumannii of 44 presumptive MBL producer isolates were positive for blaIMP gene, while blaIMP gene was not detected in Pseudomonas spp. Conclusion: All isolates of A. baumannii appeared to be resistant to carbapenem due to OMP encoded by the OprD gene, while it seems to find in some isolates of P. aeruginosa blaIMP which was detected in A. baumannii only. Some strains of A. baumannii possessed two types of resistance mechanisms to carbapenem (blaIMP + OprD genes).